Short- and Long-Term Straw Mulching and Subsoiling Affect Soil Water, Photosynthesis, and Water Use of Wheat and Maize - Yang, Yonghui; Wu, Jicheng; Du, Yan-Lei; Gao, Cuimin; Pan, Xiaoying; Tang, Darrell W. S.; van der Ploeg, Martine (Frontiers in Agronomy, 2021)
Water shortages and rainfall variability lead to a decrease in grain yield. Straw mulching (SM), subsoiling (S), and combined amendments (subsoiling + straw mulching, SS) are potential solutions for maintaining crop productivity and water resource sustainability. However, short- and long-term same application of these methods appears to result in different yield and water use efficiency outcomes. In this study, we analyze field experimental data of wheat and maize cultivation with control (conventional tillage), SM, S, and SS treatments, to assess the impact on yield and water use efficiency resulting from short- and long-term application of these practices on wheat and maize. The results show that SS treatment led to higher soil water storage (SWS) than other treatments during the regreening, jointing, booting stage of wheat and big bellmouth, filling stage of maize in short and long term experiments. Short-term increased more yield of wheat than long-term in 2014-2015 (ample rainfall) and that of maize in 2016 (low rainfall), but SS treatment in long-term led to higher SWS in the growth stage of wheat in 2015-2016 and in the growth stage of maize in 2015. In addition, SS treatment was conducive to raising net photosynthetic rate (Pn) and leaf water use efficiency (LWUE) of wheat compared to other treatments in 2015 and 2016. Conversely, Pn and LWUE of maize under S and SS treatments were higher (P<0.05) compared to other treatments in the two studied years. The yield of wheat under long-term S treatment in 2015, 9625.0 kg hm-2 was the highest (P<0.05), in two years, with a 17.7% increase compared to the control, followed by short-term S treatment. However, the water use efficiency (WUE) of wheat under long-term SS treatment in 2016 was the highest (P<0.05). The yield of maize under SM and S treatments was higher than that of other treatments, whereas the WUE of maize under long-term SS treatment in 2016 was still the highest (P<0.05). Our findings provide evidence that S and SS treatments improve crop productivity and water resource sustainability and long-term was better than the short-term.